Ethical Principles in Personal Protective Equipment (PPE) Inventory Management Decisions and Partnerships - Sawsan Saleh Al Saleh et al. (International Journal of Scientific Research and Innovative Studies, 2024)
The COVID-19 pandemic highlighted the critical importance of ethical decision-making in managing personal protective equipment (PPE) inventories and partnerships. Balancing equitable distribution, resource allocation, and partnerships with ethical principles is essential to ensure fair access and maintain public trust(1). This review explores the ethical principles underlying PPE inventory management, including equity, transparency, accountability, and stewardship. Challenges such as supply chain disruptions, prioritization of healthcare workers, and global disparities are discussed alongside strategies to integrate ethical considerations into PPE management systems. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/308 DOI: https://doi.org/10.5281/zenodo.14647831